G.S. Treuer’s ‘Apology’ of Tsar Ivan the Terrible as a Tool for Forming a Positive Image of the Russian Monarchy in Europe in the Petrine Era - Nataliya V. Eylbart (RUDN Journal of Russian History, 2022)
The article presents an analysis of the historical, political and philosophical work of outstanding German scientist, Professor Gottlieb Samuel Treuer “Apology of Ivan Vasilyevich II, Grand Duke of Moscow, usually falsely accused of tyranny,” published in Vienna in 1711. It was found that this work was one of the first papers, one way or another devoted to Russian history, published in the West in the Petrine era. During the Great Northern War the tendency to compare the reign of Ivan the Terrible and Peter I was quite clear, due to the fact that the “Baltic issue” remained valid for Russia more than a century after the failures in the Livonian War. The Russian propaganda in Europe needed to present Ivan the Terrible as a great ruler, without excessive cruelty and tyranny. The analysis conducted by the author showed that Treuer brilliantly coped with the task. In his work he proved that all the actions of Ivan the Terrible were justified by the public necessity and the morals of the Russian people. The “Apology of Ivan Vasilyevich” also contributed to the fact that some representatives of German scientific thought got carried away by Russian history. Among them were, in particular, G.F. Miller and A.L. Schlözer.